Proses Adaptasi Mahasiswa Perantauan Di UIN Ar-Raniry - Fathurrahman Helmi (SADIDA, 2022)
Abstract: This study aims to describe the causes behind the process of culture shock among overseas students in Banda Aceh to describe the process of cultural adaptation and its impact on overseas students at UIN Ar-Raniry. This research uses a qualitative approach with a phenomenological study. Data collection techniques used in this study were interviews and documentation. The results of the study explained that there were 5 stages experienced by overseas students in cultural adaptation. The two key informants had expectations when they were going abroad and had motives to study in college and achieve their goals, this was also included in the honeymoon stage. The process of interaction and lectures abroad results in a phase of frustration where there are some sick so that there is a need for adjustments to new things overseas until there are exchanges in terms of culture, ethics and meaning, these things include in the readjustment stage. At the resolution stage, the two key informants decided to stay overseas to complete their studies Keywords: Intercultural Communication, Culture Shock, Cultural Adaptation, Overseas Students Abstrak: Penelitian ini bertujuan untuk mendeskripsikan penyebab yang melatar belakangi proses terjadinya culture shock pada mahasiswa perantauan di Banda Aceh hingga mendeskripsikan proses adaptasi budaya serta dampaknya pada mahasiswa perantauan di UIN Ar-Raniry. Penelitian menggunakan pendekatan kualitatif dengan studi fenomenologi. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah wawancara dan dokumentasi. Hasil penelitian menjelaskan bahwa ada 5 tahapan yang dialami oleh mahasiswa perantau dalam adaptasi budaya. Kedua key informan memiliki ekspektasi saat akan menjalani perantauan serta punya motif untuk berkuliah dan menggapai cita-cita, hal ini juga termasuk ke dalam tahap bulan madu. Proses interaksi dan perkuliahan di perantauan mengakibatkan adanya tahap frustasi yang dimana ada yang sakit sehingga perlu adanya penyesuaian terhadap hal-hal yang baru di perantauan sampai adanya pertukaran dalam hal budaya, etika dan makna, hal-hal ini termasuk ke dalam tahap penyesuaian kembali. Pada tahap resolusi, kedua key informan memutuskan tetap bertahan di perantauan untuk menyelesaikan studinya. Kata kunci: Komunikasi Antarbudaya, Gegar Budaya, Adaptasi Budaya, Mahasiswa Perantauan